Effects of catalyst concentration and residence time on transesterification of palm oil with methanol using a 1.0 mm ID millichannel reactor - Nurul Asyikin, M.A. (Japan Institute of Energy, 2017)
Millichannel reactor designed for continuous reaction of transesterification has been studied in recent years and also attracted the focus of scientists for its capability to produce high quality biodiesel yield. The millichannel reactor exhibits many advantages, one of which includes great improvement in reaction rate, product yield, energy efficiency as well as mass and heat transfer. Therefore, the millichannel reactor has a high potential to be used for biodiesel production. In this study, transesterification of refined palm oil was carried out by using a teflon tube with an internal diameter of 1.0 mm at 21:1 methanol to oil molar ratio and 60 °C to investigate the effects of potassium hydroxide catalyst concentration (0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, and 5.0 wt), and residence time (60, 120, and 180 s) on the oil conversion and fatty acid methyl ester (FAME) yield. The transesterification using a batch reactor was also performed to compare with the millichannel reactor at conditions: 21:1 methanol to oil molar ratio, temperature of 60 °C and 0.5 wt potassium hydroxide concentration. Besides that, the process time has been varied in the ranges of 60, 120, and 180 s. In this study, the best FAME yield was obtained at 4.5 wt catalyst concentration and residence time of 180 s. As a result, the millichannel reactor revealed a higher oil conversion and FAME yield compared to the batch reactor.